Fetal cardiac function by mitral and tricuspid annular plane systolic excursion using spatio-temporal image correlation M-mode and left cardiac output in fetuses of pregestational diabetic mothers - Nathalie Jeanne Magioli Bravo-Valenzuela; Alberto Borges Peixoto; Rosiane Mattar; Edward Araujo (Korean Society of Obstetrics and Gynecology, 2021)
Objective To assess the mitral and tricuspid annular plane systolic excursions (MAPSE and TAPSE, respectively) and cardiac output (CO) in fetuses of pregnant women with pregestational diabetes mellitus (DM) using spatio-temporal image correlation M-mode (STIC-M) and virtual organ computer-aided analysis (VOCAL). Methods This study was prospective and cross-sectional. It included 45 fetuses each from mothers with pregestational DM and healthy mothers, with gestation ages ranging from 20 to 36.6 weeks. The fetal cardiac volumes were obtained and analyzed by STIC and VOCAL methods. MAPSE and TAPSE were measured by STIC-M in the apical or basal four-chamber view. The values of the right (RV) and left ventricular (LV) CO were calculated by STIC and VOCAL. Results The median values of TAPSE were 6.1 and 6.2 mm in the diabetic and control groups (P<0.001), respectively. The median values of MAPSE were 4.6 mm in the fetuses of mothers with diabetes and 4.8 mm in fetuses of healthy mothers. The fetal LV CO (60.4 L/min vs. 71.1 L/min; P=0.033, respectively) and RV CO (65.2 vs. 70.1 L/min; P=0.026, respectively) were lower in the pregestational DM group than in the control group. A significant effect of pregestational DM was observed in all functional parameters after adjusting, with fetal heart rate as covariant. There was moderate significant positive correlation between MAPSE and LV CO (r=0.53; P=0.0001) and between TAPSE and RV CO (r=0.46; P=0.0001). Conclusion Significant difference in functional parameters (TAPSE, MAPSE and LV CO) obtained by STIC and VOCAL were observed in the fetuses of the pregestational DM group compared to those of the control group.